Empreendedorismo feminino na maturidade: um estudo à luz da perspectiva institucional - Guerez, Patrícia (2017)
Entrepreneurship is acknowledged as an object and a subject of high interest of scientific community and professional/business environment. However, the focus of analysis is directed towards the identification of characteristics that make up the " being an entrepreneur" and, therefore, those that characterize women activity in this context. Thus, there is room to be explored from different cuttings and theoretical basis, in addition to the dominant discourse. In view of these arguments, this study aimed to investigate female entrepreneurship in maturity from the foundations of organizational institutionalism, admitting that despite entrepreneurship shows itself as an institution, its normative, cultural-cognitive and regulative aspects are not determinant and enforcer of behavior, but result of social construction, capable of presenting heterogeneity of meanings and contents, of being modified and/or reproduced, through interpretations and interactions carried out by/among the actors around these elements. In order to do so, the objective of this dissertation, under a recursive look, is to analyze how the elements of entrepreneurial institutional context are interpreted by mature women and integrated to their enterprises. In order to achieve this goal, this research carried out, through document analysis, a historical rescue of the institutionalized and/or dominant elements that make up the entrepreneurial scenario. Also, being operationalized under the strategy of a comparative case study of a descriptive-qualitative nature, it counted on the collaboration of the oral life history, with a focus on entrepreneurial activity, of four mature women located in two municipalities in the southeast region of Parana State, combined and complemented by non-participant observation and analysis of documents belonging to their enterprises. The outcomes indicate that entrepreneurship in the consulted scenario means the opening of a small company, following legislation precepts, being associated with certain behavioral, attitudinal and understanding modes considered as adequate, valued and significant for individuals to engage in this activity, regardless of gender. However, it demonstrates itself as a context and a social phenomenon that does not exist independently of the action and ability of mature entrepreneurs to be interpreted, being a constraint (influencer) and, at the same time, limited (influenced) by their unique trajectories and experiences of life, by other institutional contexts like “being a woman”, “being a mature person” and “being a professional” of a given sector. Such elements lead the entrepreneurial activity to a different conformity logic, adequacy and automatic reproduction of references: it is a logic of own efficiency, to be recognized as legitimate from the "entrepreneurial doing" based on the following of personal values and understandings about what they consider relevant and meaningful for the context. It is a way for these women to feel and demonstrate themselves to be economically active and useful, both for themselves and for the society that surrounds them.